2020
DOI: 10.1007/s10508-020-01644-8
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Same-Sex Sexual Practices to Family and Healthcare Providers by Men Who Have Sex with Men and Transgender Women in Nigeria

Abstract: Disclosure of same-sex sexual practices by men who have sex with men (MSM) and transgender women (TGW) may facilitate appropriate healthcare engagement, including risk assessment for HIV and other sexually transmitted infections (STIs), and negotiation of condom use with partners. However, disclosure may also generate stigma. In these cross-sectional analyses, MSM and TGW were categorized based on self-report of disclosure to family members and healthcare providers (HCP) at enrollment into the TRUST/RV368 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Other qualitative studies have shown that sexual and gender minorities avoid testing because a diagnosis of HIV or rectal STIs could lead to unintended disclosure of anal sex practices [4,31,32]. We have previously reported substantial anticipated and enacted stigma surrounding disclosure of same sex sexual practices by participants in our cohort [7,33‐35]. Despite the goal of non‐stigmatizing care delivery in our clinics, it is possible that participants who had not previously been tested for HIV had experiences that affirmed their anticipated stigma and reduced likelihood of retention.…”
Section: Discussionmentioning
confidence: 90%
“…Other qualitative studies have shown that sexual and gender minorities avoid testing because a diagnosis of HIV or rectal STIs could lead to unintended disclosure of anal sex practices [4,31,32]. We have previously reported substantial anticipated and enacted stigma surrounding disclosure of same sex sexual practices by participants in our cohort [7,33‐35]. Despite the goal of non‐stigmatizing care delivery in our clinics, it is possible that participants who had not previously been tested for HIV had experiences that affirmed their anticipated stigma and reduced likelihood of retention.…”
Section: Discussionmentioning
confidence: 90%
“…There is concern that potential beneficial effects of disclosure could be offset by adverse consequences such as societal rejection, persecution, discrimination, abandonment, separation and feelings of shame, worry or fear [17,21,39]. MSM and TGW living with HIV may face additional stigma due to same-sex sexual practices [9,[17][18][19][20]. However, we found few differences in selfreported stigma based on disclosure status.…”
Section: Discussionmentioning
confidence: 63%
“…These factors perpetuate the HIV epidemic and drive some individuals to maintain both public heterosexual relationships and private same-sex ones [8]. Nigerian MSM and TGW rarely disclose their same-sex sexual practices to healthcare providers and family members, creating barriers to receipt of appropriate healthcare services such as HIV testing and anatomically appropriate screening for other sexually transmitted infections [9]. Stigma that is deep-rooted within Nigerian culture was codified into law in 2014, when Nigeria passed the Same Sex Marriage Prohibition Act, which prohibits marriage or civil union by persons of the same sex, solemnization of same sex marriage in places of worship, direct or indirect public displays of affection by same-sex couples and registration of homosexual clubs and societies [10][11][12][13].…”
mentioning
confidence: 99%
“…Past epidemiological studies among men who have sex with men in Botswana, Namibia, Malawi, South Africa, Kenya, Senegal and Nigeria suggest that sex with women is relatively common among men who have sex with men. The reported proportion who recently had sex with women has ranged from 20% to 75% [43‐46].…”
Section: Discussionmentioning
confidence: 99%